2009
DOI: 10.17221/1670-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Study of genetic differences among Slovak Tsigai populations using microsatellite markers

Abstract: ABSTRACT:In this study genetic diversity, population structure and genetic relationships of Tsigai populations in Slovakia were investigated using microsatellite markers. Altogether 195 animals from 12 populations were genotyped for 16 microsatellites. 212 alleles were detected on the loci. The number of identified alleles per locus ranged from 11 to 35. In the majority of the populations heterozygosity deficiency and potential risks of inbreeding could be determined. High values of F ST (0.133) across all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(12 reference statements)
2
9
1
Order By: Relevance
“…Kuzsca et al (2008) found notably higher FIS values in the Kıvırcık sheep populations from Thrace and Marmara (0.374 and 0.282, respectively) than the FIS value found in the present study ( Table 2). The FIS values found for the Slovak and Hungarian Tsigai sheep breeds were also higher than those of the present study (0.252 and 0226, respectively) (Kusza et al, 2009(Kusza et al, , 2010. In contrast, the FIS values found in our study are quite high compared to the FIS values found in the Merino populations from different countries (Diez-Tascόn et al, 2000), Muzzafarnagri (Arora and Bhatia, 2004), Manchega and Churra (Calvo et al 2006(Calvo et al , 2011, Romanian Tsigai (Zăhan et al, 2011).…”
Section: Discussioncontrasting
confidence: 75%
“…Kuzsca et al (2008) found notably higher FIS values in the Kıvırcık sheep populations from Thrace and Marmara (0.374 and 0.282, respectively) than the FIS value found in the present study ( Table 2). The FIS values found for the Slovak and Hungarian Tsigai sheep breeds were also higher than those of the present study (0.252 and 0226, respectively) (Kusza et al, 2009(Kusza et al, , 2010. In contrast, the FIS values found in our study are quite high compared to the FIS values found in the Merino populations from different countries (Diez-Tascόn et al, 2000), Muzzafarnagri (Arora and Bhatia, 2004), Manchega and Churra (Calvo et al 2006(Calvo et al , 2011, Romanian Tsigai (Zăhan et al, 2011).…”
Section: Discussioncontrasting
confidence: 75%
“…18.3% for Indian sheep (Mukesh et al, 2006), 13.3% Slovak Tcigai populations (Kusza et al, 2009), 8.2% Romanian breeds (Kevorkian et al, 2010), 8.3% Bulgarian breeds (Kusza et al, 2009), 8% Austrian (Baumung et al, 2006), 6.1% Six Indian Sheep Breeds, (Arora et al, 2010), 5.7% for Alpine sheep (Dalvit et al, 2008) and European and Middle-Eastern breeds including also the Albanian sheep breeds (Peter et al, 2007), 5% for Pramenka types (Cinkulov et al, 2008), 4.6% for Ethiopian sheep (Gizaw et al, 2007), 3.7% in three Egyptian sheep and Manchega sheep (Calvo et al, 2006). Our results are similar to those reported by (Nanekarani et al, 2010) for pelt sheep breeds of Iran (0.018).…”
Section: Discussionmentioning
confidence: 99%
“…2013), or types of sheep (Santos-Silva et al, 2008;Kusza et al, 2009). Regardless of the approach used, most of the studies carried out are limited to a single country (Álvarez et al, 2004;Glowatzki-Mullis et al, 2009), while historical relationships among neighbouring sheep populations suggest the need of crossborder analyses (Tapio et al, 2005(Tapio et al, , 2010Cinkulov et al, 2008;Kusza et al, 2008;Salamon et al, 2014).…”
mentioning
confidence: 99%